The Impact of Income Inequality and Environmental Degradationon Health Outcomes in Nigeria - I, Okafor Reuben; Ezeanyeji, Clement I. (Jurnal Pesona Indonesia, 2025)
The relationship between income inequality, environmental degradation, and health outcomes has gained significant attention in recent years, particularly in developing countries like Nigeria. While economic growth has been a central focus of policy makers, its benefits are often unevenly distributed, leading to widening income gaps. This study adopted the health production function by Grossman (1972), extended by Fayissa and Gutema (2008), to examine the effects of economic, social, and environmental factors on health outcomes. Health was proxied by life expectancy and infant mortality, while key variables included CO₂ emissions, Gini coefficient, per capita GDP, energy consumption, government capital expenditure, political stability, and deforestation. The Autoregressive Distributed Lag (ARDL) model was used to capture both short- and long-run relationships, supported by cointegration tests and an error correction model. Dynamic OLS (DOLS) ensured robustness. Data from 1990–2023 were obtained from WDI, WGI, and CBN. The study's descriptive statistics reveal moderate skewness and mostly platykurtic distributions among variables, with CO₂ emissions and income inequality positively skewed, while GDP and energy consumption show negative skewness. Jarque-Bera tests confirm normality for most variables except government expenditure and political stability. Long-run ARDL results show CO₂ emissions reduce life expectancy and increase infant mortality. Income inequality surprisingly increases life expectancy but raises infant mortality. GDP per capita improves health outcomes, while government spending yields mixed effects. In the short run, CO₂ emissions and deforestation harm life expectancy, while past emissions and GDP growth improve it. Energy use has limited short-run impact. The findings underscore the importance of addressing social and environmental disparities to improve public health in Nigeria.